Economic Burden of Myocardial Infarction Combined With Dyslipidemia - Chen, Pingyu; Zhang, Mengran; Zhang, Yan; Su, Xi; Chen, Jiyan; Xu, Biao; Tao, Jianhong; Wang, Zhen; Ma, Aixia; Li, Hongchao (Frontiers in Public Health, 2021)
Background: Dyslipidemia is a common comorbidity and an important risk factor for myocardial infarction (MI). This study aimed to examine the economic burden of MI combined with dyslipidemia in China. Methods: Patients who were hospitalized due to MI combined with dyslipidemia in 2016 were enrolled. Costs were measured based on electronic medical records and questionnaires. The annual costs were analyzed by conducting descriptive statistics, univariable and multivariable analyses. Results: Data of 900 patients were analyzed, and 144 patients were dead during the follow-up. The majority of patients were aged 51 to 70 years (n=563, 62.55%) and males (n=706, 78.44%). For all-cause costs, the median annual direct medical costs, direct non-medical costs, indirect costs and total costs were RMB 13,168 (5,212-29,369), RMB 600 (0-1,750), RMB 676 (0-1,787), RMB 15,361(6,440-33,943), respectively; while for cardiovascular-related costs, the corresponding costs were RMB 12,233 (3,795-23,746), RMB 515 (0-1,680), RMB 587 (0,1,655), and RMB 14,223 (4,914-28,975), respectively. Lifestyle and complications significantly affected both all-cause costs and cardiovascular-related costs. Conclusions: Increasing attention should be paid to encourage healthy lifestyle, and evidence-based medicine should focus on optimal precautions and treatments for complications, to reduce the economic burden among MI patients with a comorbid dyslipidemia.